Video as a tool for art education: Evolution and uses of video in the classroom - Gradín Carbajal, Cristian; Ezquieta Llamas, Iciar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Video is a medium with great potential in the classroom as a gathering tool for different curricular contents, due to its motivational ability and as a vehicle for cooperative work. Its didactic integration in Spain has gone through a long journey in which the initial efforts aimed towards technology have been replaced for other more focused on media literacy and its application to active methodologies, favored by the new digital environment and portable devices.